2009
DOI: 10.1115/1.3124123
|View full text |Cite
|
Sign up to set email alerts
|

An Offshore Risk Analysis Method Using Fuzzy Bayesian Network

Abstract: The operation of an offshore installation is associated with a high level of uncertainty because it usually operates in a dynamic environment in which technical and human and organizational malfunctions may cause possible accidents. This paper proposes a fuzzy Bayesian network (FBN) approach to model causal relationships among risk factors, which may cause possible accidents in offshore operations. The FBN model explicitly represents cause-and-effect assumptions between offshore engineering system variables th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
92
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(93 citation statements)
references
References 29 publications
1
92
0
Order By: Relevance
“…These combined models have the potential to solve difficult problems. For example, Ren et al [246] developed fuzzy Bayesian networks by incorporating fuzzy logic into Bayesian network models such that the variables can be both discrete and continuous. Table 3.…”
Section: Summary Of Decision-making Methodsmentioning
confidence: 99%
“…These combined models have the potential to solve difficult problems. For example, Ren et al [246] developed fuzzy Bayesian networks by incorporating fuzzy logic into Bayesian network models such that the variables can be both discrete and continuous. Table 3.…”
Section: Summary Of Decision-making Methodsmentioning
confidence: 99%
“…Ren et al [15] indicated that the most important use of BN is in revising probabilities in light of actual observations of events. It is therefore possible to calculate the probability distribution of potential safety risks and identify the most likely potential causes in occurrence of accidents.…”
Section: Bn-based Risk Analysismentioning
confidence: 99%
“…The first group of researchers used the direct assignment method because the number of the CPs was small and the experts could easily estimate the CPs. While the subjective estimations for the CPs are usually expressed linguistically, several studies (Li and Kao 2005;Ren et al 2009;Kao et al 2011;Li et al 2012) extend the concept of a conventional BBN to allow fuzzy probabilities (fuzzy BBN). The second group of researchers (Das 2004;Baker and Mendes 2010) devised the weighted sum algorithm, which means that experts estimate less CPs, but they must additionally assess the relative strengths (weights) of the influences of the parentnodes on a child-node.…”
Section: Introductionmentioning
confidence: 99%